Adverse selection, market access and inter-market competition - Peter Hoffmann (European Central Bank (ECB), 2013)
We study the role of informed trading in a fragmented financial market under the absence of inter-market price priority. Due to frictions in traders' market access, liquidity providers on alternative trading platforms may be exposed to an increased adverse selection risk. As a consequence, the main market dominates (offers better quotes) frequently albeit charging higher transaction fees. The empirical analysis of a dataset of trading in French and German stocks suggests that trades on Chi-X, a lowcost trading platform, carry significantly more private information than those executed in the Primary Markets. Consistent with our theory, we find a negative relationship between the competitiveness of Chi-X's quotes and this excess adverse selection risk faced by liquidity providers in the cross-section. Our results have some implications for the design of best-execution policies.
Keywords: G10; G14; G24; 330; adverse selection; Inter-market competition; MiFID; Transaction fees